Alkyl Chain Grafted-Reduced Graphene Oxide Membrane for Effective Separation of Water/Alcohol Miscible Mixtures - Zhang, Hailong; Yang, Jianbo; Li, Ting; Ji, Xingxiang; Xu, Zhen; Zhu, Yaling; Liu, Libin (Frontiers in Chemistry, 2020)
Separation of water/alcohol miscible mixtures via direct filtration only under gravity is a great challenge. Here, different alkyl chain grafted-reduced graphene oxide (alkyl-RGO) is synthesized and characterized. The hydrophobic alkyl chains can considerably modify the oil-wettability of the membranes and avoid water permeation. The alkyl-RGO membrane obtained by vacuum filtration can separate water/oil immiscible mixtures. Importantly, water/alcohol miscible mixtures could also be separated solely under gravity, where alcohols efficiently permeate the alkyl-RGO membrane while water is prevented through the membrane. The separation efficiency of C12H-RGO membrane reaches up to about 0.04 vol% of water content for the case of separating an n-propanol/water (90:10 v/v) mixture with high n-propanol permeability of approx. 685 mL m-2 h-1. Molecular simulations indicate that the selective absorption ability and diffusion rate also affect water/alcohol separation. The alkyl-RGO membranes via gravity driven filtration can extend the applications of separation of water/alcohol miscible mixtures.